Gastroenteritis, sepsis, and osteomyelitis caused by Plesiomonas shigelloides in an immunocompetent host: case report and review of the literature. - Ingram, C W (1987)
We report the 11th human case of bloodstream infection with Plesiomonas shigelloides. This was the first case without any apparent underlying immunocompromising disease, and the patient was the first adult to survive the infection. We review all the extraintestinal cases associated with this organism, giving special attention to the clinical characteristics of the bloodstream infections reported previously.